2017
DOI: 10.3201/eid2304.161562
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Arthralgia Associated with Chikungunya Virus Outbreak, US Virgin Islands, December 2014–February 2016

Abstract: After the 2014–2015 outbreak of chikungunya virus in the US Virgin Islands, we compared the prevalence of persistent arthralgia among case-patients and controls. Prevalence was higher in case-patients than controls 6 and 12 months after disease onset. Continued vaccine research to prevent acute illness and long-term sequelae is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
27
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 12 publications
(14 reference statements)
5
27
1
1
Order By: Relevance
“…Only rare community-based prospective studies were found to be reported in the scientific literature concerning insular Caribbean populations. [36][37][38][39][40][41] In other world regions, past exploratory research on chronicity was conducted either prospectively on hospitalized and circumscribed patient samples or retrospectively amidst the general population. 5,[12][13][14] In light of the emerging public health burden of CHIK disease for the Caribbean region and the Americas, the present study aims mainly to provide a more comprehensive description of the epidemiological characteristics and health outcomes of chronic stage CHIK cases in the general population of Martinique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only rare community-based prospective studies were found to be reported in the scientific literature concerning insular Caribbean populations. [36][37][38][39][40][41] In other world regions, past exploratory research on chronicity was conducted either prospectively on hospitalized and circumscribed patient samples or retrospectively amidst the general population. 5,[12][13][14] In light of the emerging public health burden of CHIK disease for the Caribbean region and the Americas, the present study aims mainly to provide a more comprehensive description of the epidemiological characteristics and health outcomes of chronic stage CHIK cases in the general population of Martinique.…”
Section: Discussionmentioning
confidence: 99%
“…best knowledge, the Martinique study is the only one to examine longitudinally such a large cohort of participants (N = 509), with a broad geographical assessment of the study population all over the island (recruiting GPs were located in different areas of the territory). [36][37][38][39][40][41] The approach to gathering late illness symptoms and QoL attributes (diverse range of physical and psychological health outcomes) has also been rarely conducted by other research teams. However, less than half of the eligible subjects identified by GPs finally participated in the follow-up phase, with 705 participants (58.1%) lost to follow-up between the initial recruitment and the followup phases.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with arbovirus infections present with nonspecific signs and symptoms (Feldstein et al, 2017;Mejía and López-Vélez, 2018;Muller et al, 2017) similar to those associated with malaria, typhoid, and other bacterial infections. In Sub-Saharan Africa, arbovirus infections are often unreported, undiagnosed, or misdiagnosed and treated presumptively as malaria or typhoid.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics and consequences of CHIKV infection in Caribbean populations have been described (5,(12)(13)(14). However, only two English-speaking Caribbean countries [US Virgin Islands (USVI) and Jamaica] have published reports of the infection (15)(16)(17). Duncan et al highlighted the clinical presentation of CHIKV illness during the acute phase of the disease in Jamaica (17).…”
Section: Introductionmentioning
confidence: 99%